A multicenter randomized trial evaluating posaconazole versus fluconazole for the treatment of oropharyngeal candidiasis in subjects with HIV/AIDS - Vazquez, Jose A; Skiest, Daniel J; Nieto, Leopoldo; Northland, Rebeca; Sanne, Ian; Gogate, Jagadish; Greaves, Wayne; Isaacs, Randi (Clinical infectious diseases, 2006)
Oropharyngeal candidiasis is the most common opportunistic infection among persons infected with human immunodeficiency virus (HIV). Use of some agents is hampered by lack of efficacy, emergence of resistance, adverse events, and need for intravenous administration. Posaconazole is an extended-spectrum triazole with potent in vitro activity against Candida species, including Candida albicans, Candida glabrata, and Candida krusei (including fluconazole-resistant strains). This multicenter, randomized, evaluator-blinded study of subjects with HIV infection and oropharyngeal candidiasis compared efficacy of posaconazole with that of fluconazole. Subjects received either 200 mg of posaconazole or fluconazole oral suspension on day 1, followed by 100 mg/day for 13 days. The primary study end point--clinical success (cure or improvement) on day 14--was evaluated for 329 subjects. Durability of clinical success was evaluated on day 42. Three hundred fifty subjects received posaconazole (n = 178) or fluconazole (n = 172). Clinical success occurred in 155 (91.7%) of 169 posaconazole recipients and in 148 (92.5%) of 160 fluconazole recipients (95% confidence interval, -6.61% to 5.04%), indicating that posaconazole was not inferior to fluconazole. On day 14, mycological success was 68% in both arms, but by day 42, significantly more posaconazole recipients than fluconazole recipients continued to have mycological success (40.6% vs. 26.4%; P=.038). Fewer posaconazole recipients than fluconazole recipients experienced clinical relapse (31.5% vs. 38.2%). Adverse events were similar between treatment arms. Results demonstrate that posaconazole was as effective as fluconazole in producing a successful clinical outcome. However, posaconazole was more effective in sustaining clinical success after treatment was stopped.